A primary SERS-active interconnected Si-nanocore network for biomolecule detection with plasmonic nanosatellites as a secondary boosting mechanism. Issue 53 (3rd July 2017) - Alexander Powell, Jeffery; Venkatakrishnan, Krishnan; Tan, Bo
Abstract : We report in this study, the development of a polymorphic biosensitive Si nanocore superstructure as a SERS biosensing platform. Abstract : We report in this study, the development of a polymorphic biosensitive Si nanocore superstructure as a SERS biosensing platform. The polymorphic Si nanostructure in this study is created through ultrafast pulse laser ion-plume (UPLIP) formation and we observe enhanced detection ofl -glutathione (GSH). The distinctive polymorphic nanomaterial chemistry of the interconnected network of Si nanocores and the nanonetwork architecture of this nanostructure act as a primary enhancement booster (EF ∼ 6 × 10 3 ). With the addition of Au/AuPd nanosatellites onto the surface of the polymorphic Si nanocore structure, a significant secondary boost in GSH enhancement is observed (EF ∼ 1 × 10 5 ). The addition of noble metal nanostructures results in multi-source SERS enhancement that combines linked resonance enhancement and SPR mechanisms that both contribute to the detection and boosting of the biomolecule analyte signal. With this polymorphic Si primary booster and noble metal nanosatellite secondary booster, we have demonstrated the viability of Si nanostructures for SERS biosensing applications.